Quarter-Millimeter-Resolution Molecular Mouse Imaging with U-SPECT - Oleksandra Ivashchenko; Frans van der Have; Jose L. Villena; Harald C. Groen; Ruud M. Ramakers; Harrie H. Weinans; Freek J. Beekman (Molecular Imaging)
Limited spatial resolution of preclinical positron emission tomography (PET) and single-photon emission computed tomography (SPECT) has slowed down applications of molecular imaging in small animals. Here we present the latest-generation U-SPECT system (U-SPECT + , MILabs, Utrecht, the Netherlands) enabling radionuclide imaging of mice with quarter-millimeter resolution. The system was equipped with the newest high-resolution collimator with 0.25 mm diameter circular pinholes. It was calibrated with technetium-99 m point source measurements from which the system matrix was calculated. Images were reconstructed using pixel-based ordered subset expectation maximization (OSEM). Various phantoms and mouse SPECT scans were acquired. The reconstructed spatial resolution (the smallest visible capillary diameter in a hot-rod resolution phantom) was 0.25 mm. Knee joint images show tiny structures such as the femur epicondyle sulcus, as well as a clear separation between cortical and trabecular bone structures. In addition, time-activity curves of the lumbar spine illustrated that tracer dynamics in tiny tissue amounts could be measured. U-SPECT + allows discrimination between molecular concentrations in adjacent volumes of as small as 0.015 mL, which is significantly better than can be imaged by any existing SPECT or PET system. This increase in the level of detail makes it more and more attractive to replace ex vivo methods and allows monitoring biological processes in tiny parts of organs in vivo.